Democracy in America: Reflections on the Spirit of American Democratic Education (Journal of Education and Development, 2022)
Democracy in America is the first book to conduct a comprehensive investigation and study of the United States, the author of Tocqueville from the perspective of the French survey and exposition of American democracy, is an important material for the later study of American democracy. This paper analyzes the meaning of "democracy" of The Times, the causes of the emergence of American democracy, the existing problems and the final reflection, and provides some experience and ideas for future research